2015
DOI: 10.1186/s13046-015-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chemo- and radio-resistant phenotypes with the gap junction, adhesion and extracellular matrix in a three-dimensional culture model of soft sarcoma

Abstract: BackgroundThree-dimensional (3D) culture models are considered to recapitulate the cell microenvironment in solid tumors, including the extracellular matrix (ECM), cell-cell interactions, and signal transduction. These functions are highly correlated with cellular behaviors and contribute to resistances against chemo- and radio-therapies. However, the biochemical effects and mechanisms remain unknown in soft sarcoma. Therefore, we developed an in vitro 3D model of sarcoma to analyze the reasons of the chemo- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 39 publications
2
56
0
2
Order By: Relevance
“…also demonstrated that collagen type IV expression is upregulated in BT4C glioma tumor spheroids, whereas no significant expression was observed in monolayer cultures of BT4C cells.Further studies showed that the increased deposition of ECM proteins in spheroids can influence the response of the cells to the therapeutics Bai et al (2015). verified that the increased expression of ECM proteins (e.g., collagen and fibronectin-1) in 3D cultures of soft sarcoma (HT1080, RD, and SW872) and osteosarcoma (HOSS1) cell lines contributed for the establishment of a chemoresistant environment to doxorubicin, gemcitabine, and docetaxel.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…also demonstrated that collagen type IV expression is upregulated in BT4C glioma tumor spheroids, whereas no significant expression was observed in monolayer cultures of BT4C cells.Further studies showed that the increased deposition of ECM proteins in spheroids can influence the response of the cells to the therapeutics Bai et al (2015). verified that the increased expression of ECM proteins (e.g., collagen and fibronectin-1) in 3D cultures of soft sarcoma (HT1080, RD, and SW872) and osteosarcoma (HOSS1) cell lines contributed for the establishment of a chemoresistant environment to doxorubicin, gemcitabine, and docetaxel.…”
mentioning
confidence: 81%
“…cells were superior in spheroids(4.61, 23.55, and 103.2 µM, respectively) than in 2D cell cultures (0.078, 6.23, and 6.72 µM, respectively;Bai et al, 2015).To reduce the cell-ECM proteins interactions,Cheng, van Zandwijk, and Reid (2014) used an integrin-targeted chemotherapeutic drug (Cilengitide-synthetic peptide inhibitor of integrin αv heterodimer with high specificity for αvβ3 and αvβ5) to reduce the malignance behavior of malignant pleural mesothelioma cells (e.g., H28) spheroids. Their results demonstrated that H28 cells viability was significantly reduced because these cells display a high expression of Cilengitide target integrins.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A genetic association study published in 2012 identified a gene within one of the most conserved tumorigenesis orthologs, FN1, as associated with elbow dysplasia in Bernese Mountain Dogs [67]. Not surprisingly, the FN1 gene is expressed in soft sarcoma and osteosarcoma cells [68].…”
Section: Discussionmentioning
confidence: 99%
“…[60] Although the cytotoxicity is confirmed by ATP blocking, the maintenance of spheroid structure demonstrates that chemotherapeutic treatments have a crucial effect in ECM-related gene and protein expression, which modulates cell-cell interactions and tumor networks. [61] In fact, a broad proteomic analysis displayed a high number of species associated with doxorubicin resistance, with a focus on cathepsin D, lately implicated in several malignant phenotypes. [61] In fact, a broad proteomic analysis displayed a high number of species associated with doxorubicin resistance, with a focus on cathepsin D, lately implicated in several malignant phenotypes.…”
Section: Scaffold-free Models: Spheroidsmentioning
confidence: 99%